Daman and Diu Draft Annual Plan 2000-2001 - Planning Commission (Planning Commission, 2000)
With a view to promoting the over all development of the the country we in the U.T. of Daman & Diu we have accorded high priority to Social Sectors like Education, Medical and Public Health, Drinking Water, Irrigation for increasing production, fisheries upgrading of local skills and manpower through Vocational Training. Simultaneously an equal priority has been accorded to sectors like Power, Roads and Bridges, Rural Development .Tourism, Industries and for the weaker sections as without the development of requisite infrastructure the mere developmental thrust on the above sectors is defeated.
Union Territory of Daman and Diu, Department of Planning and Statistics